Tournamen Belajar antar Tim (Tobat) sebagai Upaya Peningkatan Pembelajaran Matakuliah Administrasi Pendidikan Jasmani - Suhadi Suhadi (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
This research is intended to know the effort of improvement for the study ofthe subject of the administration of physical education, in the Physical Education,Health, and Recreation (PJKR) Department, Faculty of Sport Science (FIK), YogyakartaState University (UNY).This research uses the method of Classroom Action Research with two cyclical actions.The first cycle consists of 4 times meetings, which is later evaluated and reflected forthe action of the second cycle. The second cycle contains 4 times meetings. Processof giving actions is equal in its step to the first cycle. Subject of this research is studentsof the 5th semester of the Physical Education, Health, and Recreation (PJKR) Department, FIK, UNY who are going through the subject of the administration of physicaleducation in 2004, amounting to 35 persons. Setting of actions is conducted in theclass during one semester (12 times of meetings). Instruments’ arrangement is inaccord with the observation guidance made by the researcher himself. The perceptions’agreement with the collaborator is done through information’s exchanges and discussions.Based on the analysis in the course of study, hence it can be concluded that the LearningTournament of Teams (TOBAT)’s pattern, indeed, can improve the learning process ofthe study of the administration of physical education, PJKR Department, FIK, UNY.This improvement is visible: students’ motivation, students’ participation in attendingthe course, students’ cooperation in solving problems, more dynamic and conductivelyclass atmosphere, and increasingly active participation of the lecturers.Keyword: Learning, The Administration of Physical Education.